Entropy generation investigation of MHD Ag– and Au–H2O nanofluid above an exponential porous stretchable surface with thermal radiation and stagnation point flow - Rashid, I.; Zubair, T.; Asjad, M. I.; Awrejcewicz, J. (Frontiers in Energy Research, 2022)
The current study presents an entropy generation investigation of magnetohydrodynamic Ag- and Au-H_2O nanofluid flows induced by an exponential stretchable sheet implanted in a porous media accompanying suction/injection and heat radiation impact. Moreover, the stagnation point flow, silver, and gold nanoparticles are considered. The consequences of ohmic heating and thermal radiation are also included as part of the heat transport examination. A physical process is transformed into a set of mathematical expressions using mathematical concepts, which can then be further simplified by using the necessary variables. Considering numerous physiological factors of interest, exact solutions for velocity and temperature profiles are calculated using similarity solution and Kummer's function method. The impact of different physical entities on the velocity field, temperature distribution, and entropy inception is investigated through graphs and numerical tables. It is noted that enhancing the values of $Ω$ reduces the entropy inception. It is observed that the entropy inception field gains due to an increment in Ec_{rt}.